LA CAÑA DE AZÚCAR Y SUS DERIVADOS EN LA HUASTECA SAN LUÍS POTOSÍ MÉXICO - Aguilar Rivera, Noé (2010)
Sugar cane is the first and most important harvest in Mexico, the sugar The change was drastic because of the larger native population and the Spaniards’ interest in other commodities such as minerals and other agricultural products. In this paper its present a summary of the evolution and strategies for the development of sugar industry in La Huasteca Potosina San Luis Potosi at The Viceroyalty of New Spain.